2022
DOI: 10.1002/ece3.8545
|View full text |Cite
|
Sign up to set email alerts
|

A domestic plant differs from its wild relative along multiple axes of within‐plant trait variability and diversity

Abstract: For 10,000 years humans have altered plant traits through domestication and ongoing crop improvement, shaping plant form and function in agroecosystems. To date, studies have focused on how these processes shape whole‐plant or average traits; however, plants also have characteristic levels of trait variability among their repeated parts, which can be heritable and mediate critical ecological interactions. Here, we examine an underappreciated scale of trait variation—among leaves, within plants—that may have ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Other quantities related to diversity, such as specialization and dominance, may also be important (Berger and Parker 1970, Martínez and Reyes-Valdés 2008), as may be measures of intramolecular complexity, which are not quantified by measures of compound dissimilarity (Richards et al 2015, Méndez-Lucio and Medina-Franco 2017, Philbin et al 2022). In addition, although we have focused on variation in phytochemical diversity at the level of individual plants, also β-diversity or diversity at the population or community is relevant for ecological function (Wetzel and Whitehead 2020, Glassmire et al 2020, Robinson et al 2022). Studies that simultaneously quantify multiple types/components of diversity are needed to examine which of these quantities are most relevant in different contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other quantities related to diversity, such as specialization and dominance, may also be important (Berger and Parker 1970, Martínez and Reyes-Valdés 2008), as may be measures of intramolecular complexity, which are not quantified by measures of compound dissimilarity (Richards et al 2015, Méndez-Lucio and Medina-Franco 2017, Philbin et al 2022). In addition, although we have focused on variation in phytochemical diversity at the level of individual plants, also β-diversity or diversity at the population or community is relevant for ecological function (Wetzel and Whitehead 2020, Glassmire et al 2020, Robinson et al 2022). Studies that simultaneously quantify multiple types/components of diversity are needed to examine which of these quantities are most relevant in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent technical advances in plant metabolomics enable the use of new analytical methods (Uthe et al 2021), which will be valuable for future insights. Finally, although most research so far has aimed to answer fundamental ecological questions, a few studies have been done in a more applied context, examining phytochemical diversity for crop species, and its potential importance for protection against pest insects (Whitehead and Poveda 2019, Espinosa-García et al 2021, Robinson et al 2022, Bernal et al 2023). Further research on this topic could increase our understanding of how considerations of chemodiversity could be utilized in agroecosystems (Silva et al 2018, Espinosa-García 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although some of this variation may be due to measurement error, it was notable that the amount of chemical trait variation differed among individual plants (Figures 2 and 3 ), suggesting that variability per se could be a target of selection. Recent evidence suggests that intraindividual variability can be a heritable trait, perhaps in large part due to transgenerational epigenetic processes, and may be adaptive in many scenarios (Herrera et al, 2021 ; Robinson et al, 2022 ; Sobral et al, 2014 ). As proposed for morphological variation (Herrera, 2017 ; Herrera et al, 2015 ), the intraindividual chemical variation reported here has the potential to increase plant fitness by improving the use of resources in a heterogeneous environment, such as variation in sunlight, water availability, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing the two previous sections: the α-, β-, and γ-phytochemical diversity are very high in ecosystems and landscapes; phytochemical diversity gets arranged in dynamic mosaics of mixtures of secondary metabolites that vary in their concentration and composition within (Robinson et al 2022) and among individuals with particular chemical morphs in populations, species with unique chemical phenotypes, or in communities whose species differ in their array of phytochemical phenotypes (Defossez et al 2021). The phytochemical mosaics select consumer species that can take advantage of them and exclude those that cannot.…”
Section: O N L I N E F I R S Tmentioning
confidence: 94%
“…The phytochemical differentiation within (Robinson et al 2022) and among individuals in a population, and its differential effects on plant consumers and their natural enemies, has been extensively documented with chemotypes, polymorphic chemical phenotypes, induced changes in the chemical phenotype after the attack of a plant antagonist, or the dynamic mosaics discussed previously (Espinosa-García & Langenheim 1991a, Wheeler 2006, Padovan et al 2013, Bustos-Segura et al 2015, Richards et al 2015, Bálint et al 2016, Meléndez-González & Espinosa-García 2018. Likewise, the differentiation among plant species in communities affecting directly or indirectly the structure of the second or third trophic levels is well documented (Becerra 2007, Richards et al 2015, Salazar et al 2018, Volf et al 2018.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%